Keterawetan Kayu Tropis dengan Proses Pengawetan Menggunakan Karbon Dioksida sebagai Pelarut Pembawa Treatability of Tropical Wood Species with Preservative Treatment Using Carbon Dioxide as a Carrier Solvent - Musrizal Muin; Astuti Arif (Masyarakat Peneliti Kayu Indonesia, 2006)
The feasibility of a preservative treatment using carbon dioxide (CO2) as a carrier solvent under various conditions was determined based on the treatability of three different commercial tropical wood species (Agathis sp., Palaquium sp., and Heritiera sp.). Treatment was conducted at six combinations of temperature and pressure (15ºC and 40 kgf/cm2, 15ºC and 60 kgf/cm2, 15ºC and 80 kgf/cm2, 25ºC and 60 kgf/cm2, 25ºC and 80 kgf/cm2, dan 35ºC and 80 kgf/cm2) with five replicates using two specimens of each wood species for each treatment. Results showed that most of these treatment conditions, except treatment at 15ºC and 40 kgf/cm2, resulted in retention levels above the Silafluofen toxic thereshold value (< 0.25 kg/m3) without any physical damages to all treated materials. The treatability of wood with CO2 impregnation was affected by the wood properties and treatment conditions